Analisis Penggunaan Aisatsu oleh Mahasiswa Prodi Pendidikan Bahasa Jepang Universitas Muhammadiyah Yogyakarta - Rosiah, Rosi (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2017)
This research conducted to analyze the use of greeting words in Japanese Language by Japanese Language Learner. In this research, 36 PBJ UMY’s Students asked to choose one of several greeting words that considered appropriate to express how they are feeling in these three following situations such as: First, when people meet somebody for the first time, second is when people leaves their town caused by their work or study, and the last is when a friend leaves their town because of their Jobs or studies. The result shows that there are many different frequencies of using greeting words in each situation.